Theory of oscillations - Zubov, Vladimir Ivanovich (Series on optimization, 1999)
This monograph deals with the controlled/non-controlled nonlinear systems of differential equations. A mathematical apparatus is developed to construct stationary conditions and to carry out studies on the behaviour of integral curves in the neighbourhood.